Optimization of Wheel Dressing Technological Parameters when Grinding Hardox 500 Steel - Danh, Tran Huu; Ky, Le Hong (Engineering, Technology & Applied Science Research, 2024)
This paper presents the research results on the influence of wheel dressing technological parameters on minimum Surface Roughness (SR) and maximum Material Removal Rate (MRR) of Hardox 500 steel. The Box-Behnken planning method with 4 factors was used, including rough wheel dressing depth ar, the number of rough wheel dressing times nr, fine wheel dressing depth af, and the number of fine wheel dressing times nf. The impact of these factors on the objectives of the grinding process was evaluated. Furthermore, an optimal grinding mode was proposed to increase MRR while minimizing SR. The proposed model can be used in industry and further research can investigate the grinding of workpiece materials with high-alloy or high-speed steel.